Investigation of anti-diabetic potential and molecular simulation studies of dihydropyrimidinone derivatives - Ilyas, Umair; Nazir, Bisma; Altaf, Reem; Muhammad, Syed Aun; Zafar, Hajra; Paiva-Santos, Ana Cláudia; Abbas, Muhammad; Duan, Yongtao (Frontiers in Endocrinology, 2022)
In an attempt to find new targets for α-amylase and α-glucosidase for the treatment of type 2 diabetes mellitus, the present study aims in determining the anti-diabetic potential of synthesized dihydropyrimidinone derivatives. The in vitro α-glucosidase and α-amylase inhibitory activity was performed and the molecular docking analysis of the ligand in the active binding site of target protein was determined. The results revealed significant percent inhibition of α-glucosidase by the compound 6-benzyl-4-(4-hydroxyphenyl)-3,4,6,7-tetrahydro-1H-pyrrolo[3,4-d]pyrimidine-2,5-dione (compound A). The active compound showed 81.99% inhibition when compared to standard ascorbic acid having percent inhibition 81.18%. The IC50 of active compound (A) showed to be 1.02 µg/ml. The molecular docking analysis revealed that the ligand bound to the active binding site of protein with the lowest binding energy of -7.5 kcal/mol that was also significant when compared to standard having -5.7 kcal/mol binding energy. In conclusion, the study revealed a potential new target against α-glucosidase to treat type 2 diabetes mellitus.